Do easy-to-read adaptations really facilitate sentence processing for adults with a lower level of education? An experimental eye-tracking study. (April 2023) - Rivero-Contreras, Miriam; Engelhardt, Paul E.; Saldaña, David
Abstract: The Easy-to-Read guidelines recommend visual support and lexical simplification to facilitate text processing, but few studies have empirically verified the efficacy of these guidelines. This study examined the influence of these recommendations on sentence processing by examining eye movements at the text- and word-level in adult readers. We tested 30 non-university adults (low education level) and 30 university adults (high education level). The experimental task consisted of 60 sentences. Half were accompanied by an image and half were not, and half contained a low-frequency word and half a high-frequency word. Results showed that visual support and lexical simplification facilitated processing in both groups of adults, and non-university adults were significantly slower than university adults at sentence processing. However, lexical simplification resulted in faster processing in the non-university adults' group. Conclusions focus on the mechanisms in which both adaptations benefit readers, and practical implications for reading comprehension. Highlights: Visual support and lexical simplification do make sentences more accessible. Using images and high-frequency words facilitates sentence processing. All adults benefit from using images and high-frequency words. Lexical simplification benefits adults with a lower education most.